2016
DOI: 10.1016/j.jogn.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health in Pregnancy

Abstract: Oral health is crucial to overall health. Because of normal physiologic changes, pregnancy is a time of particular vulnerability in terms of oral health. Pregnant women and their providers need more knowledge about the many changes that occur in the oral cavity during pregnancy. In this article we describe the importance of the recognition, prevention, and treatment of oral health problems in pregnant women. We offer educational strategies that integrate interprofessional oral health competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
1
42

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 18 publications
3
98
1
42
Order By: Relevance
“…Researches on improving women's knowledge concerning dental health care in Africa are relatively rare due to low prioritization [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches on improving women's knowledge concerning dental health care in Africa are relatively rare due to low prioritization [7].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, nurses can provide advice on preventive oral health care, including regular dental visits, and can refer pregnant women to dentists for examinations. [4][5][6][7]…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the importance of oral health during pregnancy has attracted the attention of those responsible for the caring of pregnant women and infants (foundations, agencies, health care providers, etc.) [1]. The World Health Organization (WHO) [2] has recognized that oral health is part of the preventive measures in health care for pregnant women and infants.…”
Section: Introductionmentioning
confidence: 99%
“…Oral cavity diseases, especially those infectious in nature, affect negatively not only the process of pregnancy and delivery but also the overall health of the offspring, including the condition of child's teeth [1]. Clinical studies have shown that advanced periodontal disease increases the risk of premature birth and low birth weight [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that the increase in hormone levels during pregnancy is conducive to periodontal disease [1]. Therefore, it is necessary to reinforce the importance of prevention and dental treatment.…”
Section: Introductionmentioning
confidence: 99%